(untitled) (Marketing Journal, 2026)
Abstract This article analysed modern models for optimizing regional energy supply systems. The study conducted a comparative evaluation of linear programming, stochastic optimization, and hybrid models based on artificial intelligence. Energy efficiency indicators of Uzbekistanʼs regions were assessed using statistical data. Differences in regional energy supply efficiency were identified and optimization results were evaluated. Opportunities for integrating renewable energy sources into the energy system were examined based on international data sources. The role of Smart Grid technologies and IoT sensors in energy distribution management was analysed. The findings demonstrated that hybrid AI-based models improved the efficiency of regional energy systems. The results were considered as a practical basis for improving regional energy management and optimization strategies. Keywords: energy system optimization, Smart Grid, renewable energy, artificial intelligence, regional energy efficiency, hybrid models.